Respon Negara dalam Menangkal Konten Pornografi di Media Sosial: Peluang dan Tantangan Penegakan Hukum Terhadap Konten Pornografi - Rifki Chamami Aslam (UIN Sunan Kalijaga Yogyakarta, 2024)
The government has issued laws and regulations regarding cyber offenses, but in reality, pornographic content is still widely spread in cyberspace. This article aims to examine law enforcement efforts against the spread of pornographic content on social media which is increasingly prevalent in the digital era. This article is a literature research with a normative juridical approach. Data is sourced from legislation, literature, and related online sources. The results show that the spread of pornographic content on social media occurs in various forms and motives, ranging from commercial to revenge. Existing regulations such as the Pornography Law and ITE Law have provided a legal basis to take action against criminal offenders, but the implementation is still not optimal because it faces various obstacles. The main challenges in law enforcement are the amoeba-like nature of pornographic content, the difficulty of tracking the perpetrators, and the lack of supervision of internet usage. This article contributes normatively to the realm of das sein and das solen on pornography cases in Indonesia and its enforcement efforts. Abstrak Meskipun pemerintah telah mengeluarkan peraturan perundang-undangan mengenai pelanggaran siber, namun pada kenyataanya konten-konten bermuatan pornografi masih banyak bertebaran di dunia maya. Artikel ini bertujuan untuk mengkaji upaya penegakan hukum terhadap penyebaran konten pornografi di media sosial yang semakin marak terjadi di era digital. Artikel ini adalah penelitian pustaka dengan pendekatan yuridis normatif. Data bersumber dari peraturan perundang-undangan, literatur, dan sumber online terkait. Hasil penelitian menunjukkan bahwa penyebaran konten pornografi di media sosial terjadi dalam berbagai bentuk dan motif, mulai dari komersial hingga balas dendam. Regulasi yang ada seperti UU Pornografi dan UU ITE telah memberikan landasan hukum untuk menindak pelaku pidana, namun implementasinya masih belum maksimal karena menghadapi berbagai kendala. Tantangan utama dalam penegakan hukum karena sifat konten pornografi yang terus bermunculkan bagaikan